A case of successful pregnancy in a septate uterus after discharge of decidual tissue in the second trimester. Issue 4 (11th March 2021) - Uomoto, Mari; Obata, Soichiro; Yumoto, Ami; Nakanishi, Sayuri; Sasahara, Yukiko; Otani, Masako; Miyagi, Etsuko; Aoki, Shigeru
Abstract: In pregnant patients with a divided uterine cavity, the decidual tissue on the nonpregnant side may be discharged prior to the delivery of the fetus. The pregnancy can continue if the uterine contractions and vaginal bleeding are controlled and the fetus is not in distress. Abstract : In pregnant patients with a divided uterine cavity, the decidual tissue on the nonpregnant side may be discharged prior to the delivery of the fetus. The pregnancy can continue if the uterine contractions and vaginal bleeding are controlled and the fetus is not in distress.